Analysis of the physical-mechanical properties of a photoluminescent mortar added with recycled ground glass - Nelson A. Ttito Salazar; Diego G. Vega Mercado; Jose L. Ríos Rabelo (Case Studies in Construction Materials)
This research investigates the physical and mechanical properties of a white cement mortar (standard mortar) incorporating a photoluminescent pigment (strontium aluminate) at 30 % of the cement content and recycle ground glass in proportions of 5 %, 10 %, and 15 % relative to the fine aggregate content. The study evaluates the compressive strength, flexural strength, bond strength and luminosity in the hardened state, as well as the workability (flowability) in the fresh state. Preliminary test, including particle size distribution, moisture content, bulk density, specific gravity, absorption capacity, cement density, and paste consistency, were conducted to properly design the mortar mix. The fine aggregate was sourced from the Cunyac quarry, and the cement used was white Portland Type I. The mortars were evaluated at 3, 7, and 28 days of curing. Recycled ground glass (RGG) was added to improve mechanical performance, while the photoluminescent pigment aimed to enhance luminosity retention. The study adhered to Peruvian Technical Standards (NTP) and international standards, including the Spanish UNE, American ASTM, and Chilean NCh, for material selection, testing, and analysis. The results indicate that the photoluminescent mortar containing 15 % recycled ground glass achieved the highest compressive strength (19.55 MPa) and bond strength (0.49 MPa). Meanwhile, the photoluminescent mortar with 5 % recycled ground glass exhibited the highest flexural strength (7.24 MPa), contributing to improved durability by mitigating crack formation and reducing maintenance needs. However, no significant differences in luminosity were observed among the photoluminescent mortar mixes.